2008
DOI: 10.1303/aez.2008.287
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence among populations of the white grub beetle, Dasylepida ishigakiensis (Coleoptera: Scarabaeidae), distributed in the southern part of the Ryukyu Islands of Japan, detected from mitochondrial DNA sequences

Abstract: The white grub beetle, Dasylepida ishigakiensis, was originally known only in the Yaeyama region, including Ishigaki-jima and Iriomote-jima Islands, of the southern part of the Ryukyu Islands, Japan. At the end of the 1990s, a population was discovered to occur abundantly in sugarcane fields in the Miyako region, including Miyako-jima and Irabu-jima Islands, approximately 90 km northeast of the Yaeyama region. Using specimens collected from these islands, fragments of mitochondrial DNA containing portions of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Comparison of sequences obtained in this and our previous study (Muraji et al, 2008a) confirmed that haplotypic groups A1ϩA2, B2, and C corresponded to three previously reported local populations, the Miyako population, the Ishigaki-jima natural forest population, and the Iriomote-jima population, respectively. Two others, Subgroups A3 and B1, were specific to the newly discovered Ishigaki-jima population collected on farmlands in January 2008.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Comparison of sequences obtained in this and our previous study (Muraji et al, 2008a) confirmed that haplotypic groups A1ϩA2, B2, and C corresponded to three previously reported local populations, the Miyako population, the Ishigaki-jima natural forest population, and the Iriomote-jima population, respectively. Two others, Subgroups A3 and B1, were specific to the newly discovered Ishigaki-jima population collected on farmlands in January 2008.…”
Section: Discussionsupporting
confidence: 90%
“…Commercially purchased (R)-2-butanol was used as an attractant. All other specimens were collected as described in Muraji et Two mtDNA fragments, one containing a portion of the cytochrome oxydase subunit I gene (COI) and the other containing a portion of the 16S ribosomal RNA gene (rDNA), were amplified and sequenced for all 150 individuals according to the methods described in Muraji et al (2008a), except that primer 12Rb was not used in this study. Sequences obtained from representative individuals were submitted to DDBJ/EMBL/GenBank nucleotide sequence databases (Accession numbers: AB499094-AB499121).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations